Symmetric identities of Hermite-Bernoulli polynomials and Hermite-Bernoulli numbers attached to a dirichlet character ? - Araci, Serkan; Khan, Waseem Ahmad; Nişar, Kottakkaran Sooppy; Aracı, Serkan (MDPI AG, 2018)
We aim to introduce arbitrary complex order Hermite-Bernoulli polynomials and Hermite-Bernoulli numbers attached to a Dirichlet character χ and investigate certain symmetric identities involving the polynomials, by mainly using the theory of p-adic integral on ℤp. The results presented here, being very general, are shown to reduce to yield symmetric identities for many relatively simple polynomials and numbers and some corresponding known symmetric identities. © 2018 by the authors.
Keywords: Bernoulli numbers and polynomials; Generalized bernoulli polynomials and numbers attached to a Dirichlet character χ; Generalized bernoulli polynomials and numbers of arbitrary complex order; Q-Volkenborn integral on ℤp